The Risks and Opportunities of Translating Terrestrial Biodiversity Offsets to the Marine Realm. (17th January 2018) - Shumway, Nicole; Watson, James E M; Saunders, Megan I; Maron, Martine
Abstract: Biodiversity compensation policy programs such as offsetting are increasingly being expanded to the marine realm. We reviewed the literature on biodiversity offsets and related compensatory policy to determine where marine offset policies occur. We also identified the most important differences between marine and terrestrial systems that are likely to have implications for how offsetting is conducted. We found that 77 nations had compensatory policies that enabled the use of offsets in the marine environment. Two important differences between marine and terrestrial offsets emerged: (1) biophysical differences, such as greater marine connectivity, lower likelihood of restoration success, and data paucity, and (2) social or governance differences, such as a lack of private ownership and a greater probability of leakage. We conclude that without better evaluation and innovation, it is premature to conclude that marine offsets can be effective. The lessons learned from the development of terrestrial offsets provide an opportunity to improve their application to marine ecosystems.